Nanotechnology-based strategies overcoming the challenges of retinoblastoma: a comprehensive overview and future perspectives - Shymaa Hatem; Donia Mohammed; Nermeen Ezzat (Future Journal of Pharmaceutical Sciences, 2024)
Abstract Background Retinoblastoma (RB) is a rare type of pediatric ocular cancer with difficulty in treatment and detection owing to alterations in tumor suppressor genes and the lack of focused, efficient, and cost-effective treatments. Main body of the abstract The current review presents different approaches adopted for the treatment of RB. Recently, nanodrug delivery-based systems have shown significant reported advancements in RB treatment owing to their effectiveness in delivering their cargo to the site of tumor growth, where they may induce programmed tumor cell death. Among various nanoparticulate systems employed in RB treatment are organic nanoparticles, lipid-based nanocarriers, polymeric nanoparticles, inorganic (metallic) nanocarriers (cerium oxide, iron oxide, gold and silver), and surface-tailored multifunctionalized nanocarriers. Short conclusion The current review article aims at demonstrating the superiority of nanotechnology-based formulations to traditional therapies for treatment of RB in order to enhance the bioavailability and targeting of drugs to posterior eye segment specifically, thus improving patient compliance and adherence to treatment by minimizing the number of dosing intervals and hence the likelihood of side effects.